Status of population genetic structure and distribution of Bemisia tabaci genetic groups in vegetable crops and others in India: Status of population genetic structure and distribution of Bemisia tabaci genetic groups in vegetable crops and others in India - J SRIDHAR; RK MURALI BASKARAN; PN SIVALINGAM (Journal of Oilseeds Research, 2023)
Whitefly, Bemisia tabaci is one of the polyphagous pests infesting wide variety of crop plants and is vectors of plant viruses belonging to begomivruses whose transmission efficiencies have been reported to be varying. Therefore, we have conducted a series of extensive surveys during 2019-21 to monitor and collect B. tabaci populations across the country and studied the distribution of its genetic groups. Further, PCR amplification, purification, cycle sequencing and partial CO-I gene sequencing has been done to understand population genetic structure and the distribution of genetic groups B. tabaci in India. Data analysis revealed a total of 11 genetic groups of which Asia II-3, Asia II-6 & Asia III were new to India reported for the first time from Chhattisgarh, Andhra Pradesh and Maharashtra for the first time in India. These studies will help farmers and other stakeholders to effectively manage whitefly and whitefly borne begomoviruses for increased vegetables and in turn vegetable oil production.